2019
DOI: 10.1155/2019/2508489
|View full text |Cite
|
Sign up to set email alerts
|

Boron Characterization, Distribution in Particle-Size Fractions, and Its Adsorption-Desorption Process in a Semiarid Tunisian Soil

Abstract: Boron is essential for crop growth but needed in very small amounts. The range between boron deficiency and toxicity for plants is quite narrow. These stress conditions gravely reduce yield and quality of many crop species. Therefore, understanding the factors and the reactions affecting boron availability in soil is necessary. Against this framework, our research aims to determine the available boron status in a semiarid soil of Dour Ismail irrigated perimeter (North Tunisia). The objectives are also to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…In addition to the pH of the soil solution, the amount of B absorbed by the soil is strongly determined by soil texture. It rises in proportion to the amount of clay in the soil [23]. Illite is by far the most reactive with B of the clays, while montmorillonite is only reactive at higher pH and kaolinite is the least reactive on a mass basis [45].…”
Section: Availability Of Bmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the pH of the soil solution, the amount of B absorbed by the soil is strongly determined by soil texture. It rises in proportion to the amount of clay in the soil [23]. Illite is by far the most reactive with B of the clays, while montmorillonite is only reactive at higher pH and kaolinite is the least reactive on a mass basis [45].…”
Section: Availability Of Bmentioning
confidence: 99%
“…This increase could be due to the decomposition of organic matter which produces acids such as tartaric, oxalic, citric, acetic, formic, and humic acid, which solubilized the unavailable fixed B in clay or CaCO 3 . Furthermore, some B gets complexed or chealeted with organic mattercontent and this B is released into the soil solution as the organic matter decomposes [42].Because minimal B adsorption on the mineral fraction occurs at low pH values, organic matter is one of the most important sources of B in acid soils [23].…”
Section: Availability Of Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Ayrıca, adsorbent yüzeyinin yüklenmesine göre adsorpsiyon veriminin şekillendiği bilinen bir gerçektir. Yapılan çalışmalar sonucu, bor adsorpsiyonu için en uygun pH değerleri 5-10 arası olduğu belirtilmiştir [37][38][39][40][41].…”
Section: Ph'ın Bor Adsorpsiyonu üZerindeki Etkisiunclassified
“…It was reported that excessive B restricts the production of starch or creates B-carbohydrate complexes, thereby causing delayed grain formation [ 35 ]. Because the range between critical concentrations for B deficiency and B toxicity is rather narrow, the yield and quality of many crops are often affected either by its deficiency or toxicity [ 36 , 37 ]. Boron deficiency can relatively easily be prevented or corrected via proper soil and/or foliar fertilization applications, whereas B toxicity has been more challenging to manage so far.…”
Section: Introductionmentioning
confidence: 99%